Urban lifestyle patterns: the impact of social media on quality of life - Elysia, Eda; Azmi, Novia Amirah; Fathani, Aqil Teguh; Abdullah, Zulhamri (Universitas Riau Kepulauan, 2023)
Urban lifestyle relates to the way of life in densely populated settlements and living conditions in the city. Despite differences in size, spatial structure, and social, cultural, and economic characteristics, urban communities consciously form a unity influenced by pressure and the surrounding environment. This study aims to elaborate on the pattern of urban life created using social media and its impact on quality of life (QoL), as well as the factors that influence the use of social media. This study employs a mixed methods approach, combining qualitative and quantitative methodologies. The research data is processed using the NVivo 12+ software tool to examine the lifestyle patterns of urban communities in Padang City, specifically emphasizing their utilization of social media platforms. The findings show that social media has a significant impact on shaping consumption patterns and lifestyle trends. People are exposed to social media content that influences their shopping habits, fashion, and leisure activities. However, norms, identity, and social interaction dominate in shaping lifestyle patterns and people's quality of life. The effect of social media on social interaction is not statistically significant. Thus, while social media significantly impacts urban lifestyles, other factors still play a dominant role in shaping lifestyle patterns and quality of life. In the face of social media influence, individuals in Padang City can maintain a balance and maintain their values and needs.